EDUCATIONAL PSYCHOLOGY - ITS IMPORTANCE AND THEORIES (Intent Research Scientific Journal, 2024)
The world is undergoing changes in all spheres of life and its various fields; these changes in social, economic, and industrial conditions have made life more complex and difficult and have given rise to a multitude of problems at all levels. As a result, attention to psychological knowledge and principles that govern human behavior has become paramount.